Aberrant RNA Splicing Events Driven by Mutations of RNA-Binding Proteins as Indicators for Skin Cutaneous Melanoma Prognosis - Mei, Chao; Song, Pei-Yuan; Zhang, Wei; Zhou, Hong-Hao; Li, Xi; Liu, Zhao-Qian (Frontiers in Oncology, 2020)
The worldwide incidence of skin cutaneous melanoma (SKCM) is increasing at a more rapid rate than other tumors. Aberrant alternative splicing (AS) is found to be common in cancer, however, how this process contributes to cancer prognosis still remains largely unknow. Mutations in RNA-binding proteins (RBPs) may trigger great changes in splicing process. In this study, we comprehensively analyzed DNA and RNA sequencing data and clinical information of SKCM patients, together with widespread changes in splicing patterns induced by RBP mutations. We screened mRNA expression-related and prognosis-related mutations in RBPs, and investigated the potential affections of RBP mutations on splicing patterns. Mutations in 853 RBPs were demonstrated to be correlated with splicing aberrations (p<0.01). Functional enrichment analysis revealed that these ASEs may participate in tumor progress by regulating modification process, cell cycle checkpoint, metabolic pathways, MAPK signaling, PI3K-Akt signaling and other important pathways in cancer. We also constructed a predict model based on overall survival-related AS events (OS-ASEs) affected by RBP mutations, which exhibited a good predict efficiency with the Area Under Curve of 0.989. Our work highlights the importance of RBP mutations in splicing alterations, and provides effective biomarkers for prediction of prognosis of SKCM.